Strategi Dinas Pariwisata Dalam Pengembangan Pantai Binaria di Kabupaten Buleleng Pada Masa Pandemi Covid-19 - Putra, Gede Dicky Handika; Yudartha, I Putu Dharmanu; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2023)
The Buleleng Regency Tourism Office is an institution that manages 86 DTW in Buleleng Regency. One of them is Binaria Beach which has attractive tourism potential in the form of marine tourism. However, in an effort to realize its development, there are still several problems that cannot be resolved during the Covid-19 Pandemic. Therefore, it is important to know the extent of the strategy of the Buleleng Regency Tourism Office in an effort to develop tourism on Binaria Beach during the Covid-19 Pandemic. This study uses strategic planning theory according to John M. Bryson (2016: 55-76). The method used in this research is using a qualitative descriptive method. The results show that the strategy of the Buleleng Regency Tourism Office has been going well but has not been fully handled optimally due to the Covid-19 Pandemic. Keywords: Strategy, Strategic Planning, Tourism Development, SWOT Analysis